2019
DOI: 10.1186/s13104-019-4865-0
|View full text |Cite
|
Sign up to set email alerts
|

Early onset severe preeclampsia and eclampsia in a low-resource setting, Mpilo Central Hospital, Bulawayo, Zimbabwe

Abstract: ObjectivesEarly-onset severe preeclampsia is associated with significant maternal and perinatal morbidity and mortality especially in low-resource settings, where women have limited access to antenatal care. This dataset was generated from a retrospective cross-sectional study carried out at Mpilo Central Hospital, covering the period February 1, 2016 to July 30, 2018. The aim of the study was to determine the incidence of early-onset severe preeclampsia and eclampsia, and associated risk factors in a low-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…16 Mechanistically, EOSPE was diagnosed when at least one of the following criteria was present: SBP ≥160 mmHg and/or DBP ≥110 mmHg, thrombocytopenia, impaired liver function, renal insufficiency, pulmonary edema, new-onset headache unresponsive to medications, or visual disturbances. 30,31 For the past few years, APOA1-AS expression has been found to be connected with blood pressure. For example, Abd-Elmawla MA et al found that APOA1-AS expression could be used as a predictor of atherosclerosis in SLE, which was positively correlated with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…16 Mechanistically, EOSPE was diagnosed when at least one of the following criteria was present: SBP ≥160 mmHg and/or DBP ≥110 mmHg, thrombocytopenia, impaired liver function, renal insufficiency, pulmonary edema, new-onset headache unresponsive to medications, or visual disturbances. 30,31 For the past few years, APOA1-AS expression has been found to be connected with blood pressure. For example, Abd-Elmawla MA et al found that APOA1-AS expression could be used as a predictor of atherosclerosis in SLE, which was positively correlated with hypertension.…”
Section: Discussionmentioning
confidence: 99%